Low diet quality and the risk of stroke mortality: the multiethnic cohort study - Aigner, Annette; Becher, Heiko; Jacobs, Simone; Wilkens, Lynne R.; Boushey, Carol J.; Marchand, Loic Le; Haiman, Christopher A.; Maskarinec, Gertraud (European journal of clinical nutrition, 2018)
Several diets, e.g., those low in fruits/vegetables, high in sodium, and red/processed meat, have been related to a higher stroke risk. We investigated stroke mortality associated with a priori diet-quality indices in the Multiethnic Cohort study. Based on 172,043 observations including 3548 stroke deaths, we investigated the Healthy Eating Index-2010 (HEI-2010), the Alternative HEI-2010, the alternate Mediterranean diet score, and the Dietary Approaches to Stop Hypertension index in relation to stroke mortality. Using Cox regression, we estimated adjusted population attributable risks (PAR) and hazard ratios (HR) for tertiles of the indices while adjusting for relevant confounders. The associations between all diet-quality indices and stroke mortality were consistent in direction; a low-quality diet was associated with a greater risk of stroke death, but the HEI-2010 was the strongest predictor. The PAR for stroke death based on HEI-2010 was 7.9% (95%-CI: 3.7-12.2%), indicating the preventable percentage of deaths if the total population had the same diet quality as those in the highest tertile for this diet-quality index. The lowest as compared to the highest tertile of the HEI-2010 was associated with a 1.23-fold (95%-CI: 1.13-1.34) risk. The PARs for low and medium adherence to the indices were similar by sex and follow-up time, but varied by ethnicity, with the highest PAR in Whites (15.4%) and no association in Latinos. Findings for four diet-quality indices, in particular the HEI-2010, indicated that diet quality acts as an independent risk factor for stroke mortality. Promotion of a high diet quality could have a substantial impact on the prevention of stroke deaths.